2022
DOI: 10.3389/fmed.2022.911532
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Onset of Frozen Shoulder in Middle-Aged and Elderly Subjects Within 1 Year of Discharge From a Hospitalization That Involved Intravenous Infusion: A Prospective Cohort Study

Abstract: AimTo investigate the incidence of frozen shoulder and risk factors for the onset of frozen shoulder in middle-aged and elderly subjects within 1 year of discharge from a hospitalization that involved intravenous infusion in Zhangjiagang Second People's Hospital.MethodsA total of 1,900 subjects who were discharged from a hospitalization that involved intravenous infusion in the hospital between May 2020 and September 2020 met the inclusion criteria for this study: 950 subjects had a mean daily duration of intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…Given that patients with Parkinson’s disease may have also been followed in neurological practices, one may hypothesize that adhesive capsulitis was documented in neurological and not in general practices, potentially biasing the present association. The relationship between hypertension and adhesive capsulitis remains under debate, as previous studies have reported positive [ 24 ] and null associations [ 8 , 11 , 35 ]. In this context, more data are warranted on the potential hypertension–adhesive capsulitis relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Given that patients with Parkinson’s disease may have also been followed in neurological practices, one may hypothesize that adhesive capsulitis was documented in neurological and not in general practices, potentially biasing the present association. The relationship between hypertension and adhesive capsulitis remains under debate, as previous studies have reported positive [ 24 ] and null associations [ 8 , 11 , 35 ]. In this context, more data are warranted on the potential hypertension–adhesive capsulitis relationship.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Univariate analysis of the Cao, 2022 study revealed a strong connection between hypertension and the start of a frozen shoulder (p = 0.009). 24 The mechanism arising from inflammation, with cytokine proliferation leading to an increase in fibroblast proliferation, blood flow increasing in patients with hypertension, and enhanced vascularization, may explain the patient’s pain. 25 In our case, patients with hypertension showed more painful than non-comorbid patients.…”
Section: Discussionmentioning
confidence: 99%
“…Angiologische Interventionen sind ebenfalls an der Entstehung der Schultersteife beteiligt. Neben der klassischen kardialen Katheterisierung, können intravenöse Infusionen eine Schultersteife begünstigen [1,55]…”
Section: Medizinische Therapienunclassified
“…Angiological interventions are also implicated in the development of shoulder stiffness. In addition to classic cardiac catheterisation, intravenous infusions can also promote shoulder stiffness [1,55]…”
Section: Medical Treatmentsmentioning
confidence: 99%